On the taxonomy of Afrotropical Coleophoridae (II) (Lepidoptera, Coleophoridae) - Baldizzone, Giorgio; Wolf, Hugo W. Van Der (Zootaxa, 2015)
Eight new species of the genus Coleophora Hübner, 1822 are described: Coleophora kenyaensis sp. nov., C. vansoni sp. nov., C. elegans sp. nov., C. namaqua sp. nov., C. kamiesella sp. nov., C. kunenensis sp. nov., C. creola sp. nov., and C. hirsutella sp. nov. The genitalia of three previously described species are described and illustrated for the first time: Coleophora niphocrossa Meyrick, 1920, C. enchitis Meyrick, 1920 and C. textoria Meyrick, 1921. The larval case of C. enchitis is illustrated and data about its biology are given.